Determine the Green function and express the solution as a definite integral
-(y''+y)=f(x), y'(0)=0, y(1)=0
We remind that the Green function is a function "G(x,s)" such that "y(x)=\\int_{x_0}^xG(x,s)f(s)ds".
We rewrite the equation as "z=y'" , "-z'-y=f(x)". It can be rewritten as: "\\left\\{\\right.\\begin{matrix}\n y'=z \\\\\n z'=-y-f(x)\n\\end{matrix}"
It can be rewritten as: "\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)\\left(\\begin{matrix}\n y'&z'\\\\\n 0&0\n\\end{matrix}\\right)=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)\\left(\\begin{matrix}\n y&z\\\\\n 0&0\n\\end{matrix}\\right)\\left(\\begin{matrix}\n 0&-1\\\\\n 1&0\n\\end{matrix}\\right)+\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)\\left(\\begin{matrix}\n 0&-f(x)\\\\\n 0&0\n\\end{matrix}\\right)"
It is enough to solve the problem: "A'=A\\sigma+F", where "A=\\left(\\begin{matrix}\n y&z\\\\\n 0&0\n\\end{matrix}\\right)", "\\sigma=\\left(\\begin{matrix}\n 0&-1\\\\\n 1&0\n\\end{matrix}\\right)" "F=\\left(\\begin{matrix}\n 0&-f(x)\\\\\n 0&0\n\\end{matrix}\\right)". The solution of equation "A'=A\\sigma" is "A=Ce^{\\sigma t}" with matrix "C". We suppose that "C=C(t)". We substitute and get: "C'e^{\\sigma t}+Ce^{\\sigma t}{\\sigma}=Ce^{\\sigma t}{\\sigma}+F". We get: "C=\\int Fe^{-\\sigma t}dt+K" with a constant matrix "K=\\left(\\begin{array}{cc}k_{11}&k_{12}\\\\k_{21}&k_{22}\\end{array}\\right)." Thus, "A=(\\int Fe^{-\\sigma t}dt+K)e^{\\sigma t}". We notice that "y=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)\\left(\\begin{matrix}\n y&z\\\\\n 0&0\n\\end{matrix}\\right)\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)" . Thus, "y=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)(\\int Fe^{-\\sigma t}dt+K)e^{\\sigma t}\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)". From the latter we can find the Green function.
Remind that "e^{\\sigma t}=1+\\sigma t+\\frac{(\\sigma t)^2}{2!}+\\frac{(\\sigma t)^3}{3!}+..." Compute powers of matrix "\\sigma": "\\sigma^2=\\sigma=\\left(\\begin{matrix}\n -1&0\\\\\n 0&-1\n\\end{matrix}\\right)=-I". Thus, "e^{-\\sigma t}=I(1-\\frac{(-t)^2}{2!}+\\frac{(-t)^4}{4!}).-+...+\\sigma(-t-\\frac{(-t)^3}{3!}+\\frac{(-t)^5}{5!})+...=Icos(\\,-t)+\\sigma\\,sin(-\\,t)"
As a result, we get:"y=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)(\\int Fe^{-\\sigma t}dt+K)e^{\\sigma x}\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)(\\int \\left(\\begin{matrix}\n 0&-f(t)\\\\\n 0&0\n\\end{matrix}\\right)\\left(\\begin{matrix}\n cos\\,t&sin\\,t\\\\\n -sin\\,t&cos\\,t\n\\end{matrix}\\right)dt+\\left(\\begin{array}{cc}k_{11}&k_{12}\\\\k_{21}&k_{22}\\end{array}\\right))e^{\\sigma x}\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right) \\left(\\begin{matrix}\n \\int f(t)\\,sin\\,t \\,dt+k_{11}&-\\int f(t)\\,cos\\,t\\,dt+k_{12}\\\\\n k_{21}&k_{22}\\end{matrix}\\right)\\left(\\begin{matrix}\n cos\\,x&-sin\\,x\\\\\n sin\\,x&cos\\,x\n\\end{matrix}\\right)\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)A\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)=\\left(\\begin{matrix}\n1&0\n \\end{matrix}\\right)\\left(\\begin{matrix}\n a_{11}&a_{12}\\\\\n a_{21}&a_{22}\n\\end{matrix}\\right)\\left(\\begin{matrix}\n 1\\\\\n 0\n\\end{matrix}\\right)=a_{11}".
"a_{11}= cos\\,x(\\int f(t)\\,sin\\,t \\,dt+k_{11})+sin\\,x(-\\int f(t)\\,cos\\,t\\,dt+k_{12})=k_{11} cos\\,x+k_{12}sin\\,x+\\int f(t)(cos\\,x\\,sin\\,t-sin\\,xcos\\,t) \\,dt"
As we can see, "k_{11} cos\\,x+k_{12}sin\\,x" is a solution of the homogenous problem "y''+y=0". Therefore, we set "k_{11}=k_{12}=0" and receive that the Green function is: "G(x,t)=cos\\,x\\,sin\\,t-sin\\,xcos\\,t"
Comments
Leave a comment